TOKUSUKE UTSUGI’S SEXUAL MASOCHISM IN JUNICHIRO TANIZAKI’S DIARY OF A MAD OLD MAN - Muhid, Abdul; Alfisuma, Meria Zakiah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
This paper discussed one of the sexual disorders called sexual masochism through literary study. By discussing one of the novels by Junichiro Tanizaki entitled Diary of a Mad Old Man, the writers have some objectives in writing this paper. First, to describe sexual masochism experienced by Tokusuke Utsugi through the symptoms reflected on his behavior and way of thinking. Second, to uncover the causal factor and the impact of Tokusuke Utsugi' sexual masochism in Junichiro Tanizaki's Diary of a Mad Old Man. This study uses descriptive qualitative methods; all of the data are obtained by doing library research (literature review). The analysis result shows Tokusuke Utsugi was a sexual masochist, ie man who has sexual deviations by symptoms experienced such as 1) Tokusuke Utsugi’s sexual desire resulting from torture or acceptance of pain from Satsuko, 2) Tokusuke Utsugi’s sexual desire resulting from suffering due to his various illnesses, 3) Tokusuke Utsugi’s sexual desire resulting from the insult he received from Satsuko. Sexual masochism suffered by Tokusuke Utsugi is the result of burial deviant sexual fantasies. As a result of the fulfillment of a deviant sexual desire, he was willing to do crazy things to satisfy his sexual desire.